PREVALENCE AND RISK FACTOR OF LOW BACK PAIN IN FISHERMAN IN BENGKULU CITY: A CROSS SECTIONAL STUDY - -, Rizkianti Anggraini; Fitria, Salsa; Nasution, Ahmad Azmi; Zainuddin, Zayadi; Sudjatmoko, Azhar Firman (UNIVERSITAS BENGKULU, 2024)
Background: Low back pain (pain or discomfort below the costal margin and above the inferior gluteal fold accompanied by leg pain or not) is considered one of the work-related musculoskeletal disorders. Aims and scope of paper:Identifying the prevalence and risk factors for lower back pain in fishermen in Bengkulu City. Methods: A total of 93 fishermen were included in the study, selected using a simple random sampling technique. An observational analytical method with a cross-sectional approach was employed in this study, and data analysis was performed using the Kolmogorov Smirnov for normality test and the Pearson test for bivariate analysis. Result: In Bengkulu City, low back pain was experienced by a total of 68 fishermen (73.12%) and disability was experienced by 39 fishermen (41.9%). The dominant age group in this study was 20 – 39 years with 42 fishermen (45.16%). Normal BMI dominated with 50 fishermen (53.76%). Work duration of more than 7 hours was reported by 70 fishermen (75.26%). Consumption of 1-20 cigarettes per day was reported by 68 fishermen (73.12%). Awkward postures with a high risk level were experienced by 41 fishermen (44.08%). Conclusion: The risk factors potentially involved in this case are age and BMI. Meanwhile, the incidence of low back pain was found to have no significant relationship with work duration (p = 0.635), smoking habit (p = 0.58), or work posture (p = 0.063).